PROSPEK USAHA PEMBUATAN KERUPUK IKAN GABUS - Siti Erlina; Inda Ilma Ifada; Supianor Supianor (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
Catfish is one of the potential fish that contains nutrients and albumin were quite high. To provide added value and increase the types of processed fish that can be consumed by all circles both parents, adults and children then performed Catfish processing in the form of fish crackers. In the city of Banjarmasin are small and medium enterprises that undertake the manufacture of Catfish Crackers with the highest number being in the Village Kuin cerucuk which is a tourist area. So far, these efforts are inherited from parents and yet so developed rapidly, while the area is a tourist center that conducted this study to determine Prospects Making Catfish Crackers from technical and economic aspects. Methods of research using census with descriptive and financial analysis. The process of making Catfish Crackers namely: mashed, separation of meat and bone fish, mixing spices, kneading, molding, steaming, cooling, cutting and drying. A total cost of Rp 2,590,008, - with a production of 53 kg, acceptance of Rp 3,767,272, - / month, an income of Rp 1,515,112, - / month, a profit of Rp 1,177,264, - / month, RCR 1,47, BEP price of Rp 48 370, - and BEP production of 37 kg.